Competitive spirit (London : Video Arts, 1991)
Status seeking, empire building and interdepartmental politics - they're the most familiar, but least documented problems of corporate management. The video provides an extremely uncomfortable exposition of just how dangerous they can be
Keywords: Problem solving; Creative thinking; Communication in management